Sustainability Analysis of Environmental Comfort and Building Information Modeling in Buildings: State of the Art and Future Trends - Thayná F. Ramos; Alex Ximenes Naves; Dieter Boer; Assed N. Haddad; Mohammad K. Najjar (Eng, 2024)
Environmental comfort involves creating comfortable and healthy indoor environments, taking into account the climate characteristics of the built environment. The novelty herein is to define the challenges of using Building Information Modeling (BIM) to assess the three dimensions of environmental comfort: thermal comfort, visual comfort, and acoustic comfort. This work conducts a bibliometric review, using the VOSviewer software (version 1.6.20) and the GPSV website, and a bibliographic review of recently published articles in the field. This paper aims to identify the dimensions of sustainability with a focus on environmental comfort and the themes associated with these dimensions, recognize the limitations of the research, and propose recommendations for future work. The results of this work define the limitations related to the three dimensions of environmental comfort and recommend establishing a reliable database, integrating BIM with parameters that could interfere with the quality of the indoor environment.